Telemonitoring and self-management in the control of hypertension (TASMINH2): a cost-effectiveness analysis. (29th August 2020) - Kaambwa, Billingsley; Bryan, Stirling; Jowett, Sue; Mant, Jonathan; Bray, Emma P; Hobbs, FD Richard; Holder, Roger; Jones, Miren I; Little, Paul; Williams, Bryan; McManus, Richard J
Abstract: Aims: Self-monitoring and self-titration of antihypertensives (self-management) is a novel intervention which improves blood pressure control. However, little evidence exists regarding the cost-effectiveness of self-monitoring of blood pressure in general and self-management in particular. This study aimed to evaluate whether self-management of hypertension was cost-effective. Design and methods: A cohort Markov model-based probabilistic cost-effectiveness analysis was undertaken extrapolating to up to 35 years from cost and outcome data collected from the telemonitoring and self-management in hypertension trial (TASMINH2). Self-management of hypertension was compared with usual care in terms of lifetime costs, quality adjusted life years and cost-effectiveness using a UK Health Service perspective. Sensitivity analyses examined the effect of different time horizons and reduced effectiveness over time from self-management. Results: In the long-term, when compared with usual care, self-management was more effective by 0.24 and 0.12 quality adjusted life years (QALYs) gained per patient for men and women, respectively. The resultant incremental cost-effectiveness ratio for self-management was £1624 per QALY for men and £4923 per QALY for women. There was at least a 99% chance of the intervention being cost-effective for both sexes at a willingness to pay threshold of £20, 000 per QALY gained. These results were robust to sensitivity analyses around the assumptions made, provided that the effects of self-management lasted at least two years for men and five years for women. Conclusion: Self-monitoring with self-titration of antihypertensives and telemonitoring of blood pressure measurements not only reduces blood pressure, compared with usual care, but also represents a cost-effective use of health care resources.